The effect of operating conditions on the residence time distribution and axial dispersion coefficient of a cohesive powder in a rotary kiln. (2nd February 2017) - Paredes, Ingrid J.; Yohannes, Bereket; Emady, Heather; Glasser, Benjamin J.; Borghard, William G.; Muzzio, Fernando; Cuitiño, Alberto M.; Beeckman, Jean; Ilias, Samia; Podsiadlo, Paul; Jezek, Eric; Baumgartner, Joseph
Abstract: While continuous rotary calcination is a widely used thermal treatment in large-scale catalyst manufacturing, the process's heat and mass transfer mechanisms remain a challenge to characterize and to predict. Thus, the goal of this research is to improve fundamental understanding of rotary calcination to aid in the creation of a scientific methodology for process design and scale-up. For successful calcination to occur, the residence time of the particles must exceed the time required for heating and calcination at a set temperature. The optimal residence time therefore depends on both of these competing time scales, each of which is function of feed material properties, kiln geometry and kiln operating conditions. For uniform treatment of the feed, the particles must also exhibit low axial dispersion. In this work, the residence time distribution and axial dispersion coefficient for a dry cohesive fluid cracking catalyst powder were measured in a pilot plant kiln using a tracer study developed by Danckwerts. Results were successfully matched to the Taylor fit of the axial dispersion model and the Sullivan prediction for mean residence time. It was found that an increase in feed rate, kiln incline and rotary speed decreased mean residence time and overall axial dispersion. Such results have been established previously for free-flowing material like millimeter-sized extrudates, but have not been previously reported for the cohesive powders such as the one used in our work. As in free-flowing material, the axial dispersion coefficient was found to vary with kiln conditions. The values of the axial dispersion coefficients were lower for the powder than for free-flowing material, showing a dependency of axial dispersion on material properties as well as bulk flow behavior. Highlights: The Taylor fit to the axial dispersion model applies to cohesive systems. The axial dispersion coefficient was found to depend on kiln operating conditions. The accuracy of Sullivan's predictive model depends on kiln operating conditions.